Poverty reduction as a factor of ensuring food security in Kazakhstan - Berstembayeva, R.K.; Tleuzhanova, D.A.; Sarzhanov, D.K.; Amangeldiyeva, Zh.A. (Karagandy University of the name of acad. E.A. Buketov, 2023)
Object: One of the key factors of economic security is the economic availability of food. This directly affects the problem of poverty reduction. Today, in Kazakhstan, the decline in real incomes of the population threatens the possibility of meeting the need for high-quality nutrition of citizens. The purpose of the study is to assess the level of poverty in Kazakhstan and develop measures to reduce it. Methods: The research methods were: systematic, the method of economic and statistical data processing, expert evaluation, the method of multidimensional comparative analysis of the level of poverty in the context of the regions of Kazakhstan and the republic as a whole. Findings: It is revealed that Kazakhstan ranks 32nd in the ranking of 113 countries in the world on food security. This is largely determined by the decrease in the availability of food products as a result of the lagging income of the population from the increase in food prices. The decrease in the economic availability of food occurs as a result of the increase in poverty indicators. The methodology for assessing poverty based on the consumer basket does not reflect the real picture and needs to be adjusted. The underestimation of the subsistence minimum directly determines the amount of social payments from the state budget for vulnerable segments of the population, which further aggravates the growth of the number of poor. Conclusions: Based on the analysis, a number of recommendations aimed at combating poverty, including organizational, legislative and financial instruments, are presented. In particular, it is proposed to revise the methodology for assessing the consumer basket; set the poverty line by the subsistence minimum, as is customary in most countries and recommended by international experts; develop state programs to promote youth employment; increase the responsibility of local executive bodies for the implementation of employment programs and the development of regional employment centers.
Кедейлікті азайту Қазақстандағы азық түлік қауіпсіздігін қамтамасыз ету факторы ретінде
Сокращение бедности как фактор обеспечения продовольственной безопасности в Казахстане
Keywords: food security; economic accessibility of food; subsistence minimum; consumer basket; poverty level